Perceval sutureless aortic valve replacement after ascending aortic replacement. Issue 12 (5th December 2021) - Yajima, Shin; Satoh, Ayaka; Sekiya, Naosumi; Yamazaki, Sachiko; Uemura, Hisashi; Tanaka, Hiroe; Yamamura, Mitsuhiro; Sakaguchi, Taichi
Abstract: In patients with a narrow sinotubular junction, small sinus of Valsalva, or extensibility loss in the aortic root, aortic valve replacement (AVR) with a standard valve is challenging due to limited surgical field. Detailed preoperative measurements of the aortic root render performing AVR using the Perceval valve easy. Abstract : In patients undergoing previous ascending aortic replacement, AVR using the Perceval valve can be performed with aortotomy on the graft and without any manipulation of the aortic root. The optimal valve size can be selected preoperatively if detailed aortic annulus measurement was made.